Aplikasi Media Evaluasi Pembelajaran Pelajaran TIK Berbasis Animasi Multimedia Untuk Anak-Anak Kelas 1 SD - Septanto, Henri; Lesmana, Tedi (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
The impact of advances in Information and Communication Technology include the use ofmultimedia facilities in teaching and learning activities. At present teaching materials and evaluationtools in the form of multimedia-based applications are widely used, ranging from formal educationto elementary, secondary, higher and non-formal education. Evaluation of learning in the form ofexaminations or tests is one of the measuring tools used by teachers to test the success of teachingand learning activities, but there are still many who have not utilized information and communicationtechnology in the form of multimedia devices even though facilities have been provided by theinstitutions where they work. In general, the Teachers prefer to use conventional media in the formof question papers compared to multimedia-based questions, this is what inspires writers to createmultimedia-based ICT Lesson evaluation applications using Adobe Flash. The objectives of this studyare: (1) helping elementary school teachers provide evaluation questions, (2) making it easier forGrade 1 children in working on evaluation questions, The research method used is the Prototypingprocess model. The results of this study are an application of learning evaluation based on multimediaanimation, published in national journals that are not accredited.